Famines and the making of heritage - Corporaal, Marguérite 1973-; Zwarte, Ingrid de 1988- (Routledge, Taylor & Francis Group, 2024)
"This volume is the first book to bring together ground-breaking research on the role of European famines in the 19th and 20th centuries in relation to heritage making, museology, commemoration, education and monument creation. The presence of these famine pasts continues to be felt in the immediate present: in traditional and social media, museums, and class rooms, as well as through monuments and activities surrounding commemorations. Furthermore, these European famines have often been politicised in public debates, such as those regarding the recent economic crisis, the ongoing COVID-19 pandemic and refugee crisis, or the current war instigated by Russia in Ukraine. The book chapters, written by famine experts from across Europe and North America, adopt a pioneering transnational perspective, and discuss issues such as contestable and repressed heritage, materiality, dark tourism, education on famines, oral history, multidirectional memory, and visceral empathy.
Keywords: Geschichte 1800-1950; Hungersnot; Europa; Famines / Europe / History / 19th century; Famines / Europe / History / 20th century; Europe / Economic conditions / 19th century; Europe / Economic conditions / 20th century; Famines / Europe / Histoire / 19e siècle; Famines / Europe / Histoire / 20e siècle; Europe / Conditions économiques / 1789-1900; Europe / Conditions économiques / 20e siècle